Documentación de la pasantía: Los Yanaconas, sus característica y contribuciones a la tradición constructiva (2020)
This research aims to collect and analyze information related to the Yanacona people, especially that referring to their constructive traditions, based on their historical antecedents and their liaison with the Inca empire. Talk about indigenous tradition implies entering into the knowledge of its characteristics and analyzing them from historical, circumstantial and temporal perspectives. Hence, this research is framed in a qualitative paradigm, which allows the description and investigation of social dynamics and realities, which will be analyzed in the light of a theoretical conceptualization; In such a way that the reading of existing bibliography about the Yanaconas will be used as the main information gathering tool, with the aim of accessing a closer panorama of the study subjects represented by the Yanacona people and their life experiences through of history.